Antioxidant and Anti-hypertensive Activity, and Cytotoxicity of Amino Acids-Enriched Salt Recovered from Codfish (Gadus morhua L.) Salting Wastewater - Ferraro, Vincenza; Sousa, Sérgio C.; Marques, Cláudia; Calhau, Conceição; Pintado, Manuela E. (Waste and Biomass Valorization, 2015)
Wastewater from codfish (Gadus morhua L.) salting represents an environmental concern and a cost for processors which must address the disposal. Amino acids-enriched liquid salts (NaCl) were recovered from that effluent and were assessed for the antioxidant and anti-hypertensive activity, and for cytotoxicity to evaluate the possibility to be considered as a functional ingredient. Two samples were evaluated: a hypertonic salt at 15 g/L NaCl and 3 g/L amino acids, and an isotonic salt at 9 g/L NaCl and 1.8 g/L amino acids, obtained by diluting the former. Both samples showed moderate antioxidant activity; the values obtained for each assay depended on the mechanism of radical inhibition as well as on amino acids and NaCl concentration. No pro-oxidant effects on DNA were observed. Both salts demonstrated a significant anti-hypertensive activity with IC50 11 µg/mL for the hypertonic and 7.4 µg/mL for the isotonic sample. For the isotonic salt no cytotoxic effects on intestinal cells were noticed over 180 min, and on hepatic cells up to 70 min. The biological activity showed by the amino acids-enriched salt could prompt the application as a functional ingredient and drive the valorisation of the codfish salting wastewater.